The motivation of English language teachers in Greek secondary schools - Gheralis-Roussos, Eleni (2003)
This thesis addresses a largely uncharted area within language motivation research, which is the motivation of teachers of English as a foreign language (EFL). A qualitative research approach was employed to identify and document different motivational influences affecting EFL teacher motivation. The method of analysis employed in our dataset, which consisted of a series of in-depth qualitative interviews with Greek state EFL and non-EFL teachers, followed the principles of grounded theory. Most of the findings coincided with insights from other teacher motivation studies; namely that the intrinsic aspect of teaching was the most satisfying, and thus the most motivating, of all motivational factors, while the extrinsic aspect both within and outside the school context was one of the main contributors to teacher demotivation. However, the findings have also highlighted an area that had not been paid much attention to in the literature, the temporal dimension of teacher motivation, which plays an important role in the development and motivation of the teacher due to the fact that teaching as a profession is a lifelong engagement. The study has offered several insights into EFL teacher motivation and the results are hoped to facilitate the alleviation of the problem of teacher demotivation and dissatisfaction. The thesis concludes with implications for future work in this novel area of research.